Mapping N-linked glycosylation of carbohydrate-active enzymes in the secretome of Aspergillus nidulans grown on lignocellulose - Rubio, Marcelo Ventura (Biotechnol Biofuels, 2016)
BACKGROUND: The genus Aspergillus includes microorganisms that naturally degrade lignocellulosic biomass, secreting large amounts of carbohydrate-active enzymes (CAZymes) that characterize their saprophyte lifestyle. Aspergillus has the capacity to perform post-translational modifications (PTM), which provides an additional advantage for the use of these organisms as a host for the production of heterologous proteins. In this study, the N-linked glycosylation of CAZymes identified in the secretome of Aspergillus nidulans grown on lignocellulose was mapped. RESULTS: Aspergillus nidulans was grown in glucose, xylan and pretreated sugarcane bagasse (SCB) for 96 h, after which glycoproteomics and glycomics were carried out on the extracellular proteins (secretome). A total of 265 proteins were identified, with 153, 210 and 182 proteins in the glucose, xylan and SCB substrates, respectively. CAZymes corresponded to more than 50 % of the total secretome in xylan and SCB. A total of 182 N-glycosylation sites were identified, of which 121 were detected in 67 CAZymes. A prevalence of the N-glyc sequon N-X-T (72.2 %) was observed in N-glyc sites compared with N-X-S (27.8 %). The amino acids flanking the validated N-glyc sites were mainly composed of hydrophobic and polar uncharged amino acids. Selected proteins were evaluated for conservation of the N-glyc sites in Aspergilli homologous proteins, but a pattern of conservation was not observed. A global analysis of N-glycans released from the proteins secreted by A. nidulans was also performed. While the proportion of N-glycans with Hex(5) to Hex(9) was similar in the xylan condition, a prevalence of Hex(5) was observed in the SCB and glucose conditions. CONCLUSIONS: The most common and frequent N-glycosylated motifs, an overview of the N-glycosylation of the CAZymes and the number of mannoses found in N-glycans were analyzed. There are many bottlenecks in protein production by filamentous fungi, such as folding, transport by vesicles and secretion, but N-glycosylation in the correct context is a fundamental event for defining the high levels of secretion of target proteins. A comprehensive analysis of the protein glycosylation processes in A. nidulans will assist with a better understanding of glycoprotein structures, profiles, activities and functions. This knowledge can help in the optimization of heterologous expression and protein secretion in the fungal host. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-016-0580-4) contains supplementary material, which is available to authorized users.